Mempertahankan Eksistensi Kampung Basen Sebagai Kampung Wisata Kerajinan Perak melalui Rumah Produktif di Era Bisnis Online - Tutun Seliari; Wiyatiningsih Wiyatiningsih (Jurnal Pariwisata Terapan, 2018)
Tourism Kampung is an alternative tourist destination for tourists who want to vacation in urban areas. Basen is a tourism kampung that was inaugurated since 2011. Basen Tourism Kampung has a major attraction as a kampung of silver artisans and silver sellers. The issues discussed in this paper is the existence of Basen as a tourism kampung that has the main attractions of silver handicrafts, not only silver products but also tourists can be involved in the process of making silver made in the occupancy community of Basen. Problems arise when the online media created a virtual transaction phenomenon of buyers and sellers, so without the physical showrooms the silver artisans and silver sellers can commercialize their products. The method used in this research is descriptive method with qualitative approach. Survey conducted to collect data. The survey targets are silver artisans and silver sellers. In-depth interviews were conducted on silver artisans and silver sellers to obtain the accuracy of the data. The result of the research shows that the important aspect in the existence of silver handicrafts in Basen is the existence of productive house in Kampung Basen and community of silver artisans and silver sellers. The productive house of the community in Kampung Basen is not only used as occupancy but also the activity of silver handicraft which became the main attraction in Basen Tourism Kampung.